PENGARUH SPORT EDUCATION MODEL DALAM PEMBELAJARAN BOLA VOLI TERHADAP SIKAP PERCAYA DIRI SISWA SEKOLAH MENENGAH PERTAMA - Tazra Fiddinnia Robin; Fahrudin; Ega Trisna Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine, analyze, and identify the Influence of SportEducation Mode in Volleyball Learning on the Self-Confidence of Students atSMPN 4 Klari. This study was conducted using a quantitative approach and usingan experimental method with a research design of The Randomized Pretest andPosttest Control Group Design. The population in this study was class VIII ofSMPN 4 Klari totaling 478 students. The sample used in this study was ClusterRandom Sampling, after the lottery was conducted, the sample in the study wasclass VIII I and VIII J totaling 80 students. The research instrument used a studentself-confidence attitude questionnaire instrument. The results of this study werethat the average before and after treatment experienced a significant increase,namely the mean pretest 135.10 to the mean posttest 149.18. The results of thecalculation of the Paired Sample T Test hypothesis test with the data obtainedfrom this study were a significance value (2-tailed) of 0.000 < 0.05. While theresults of the calculation of the Independent Samples T Test hypothesis test,namely the data obtained from this study are a significance value (2-tailed) of0.000 < 0.05. This means that from the two hypothesis tests there is a significantinfluence between the average value before treatment and the average value aftertreatment. It can be concluded that the Sport Education Model can have an effecton volleyball learning on the self-confidence of class VIII students of SMPN 4 Klari.